The Influence of Lifestyle, Promotion, and Product Quality on Purchasing Decisions on Nu Skin TR90 Products in Surabaya. - Theodora Ketlinia; Ugy Soebiantoro (Indonesian Journal of Business Analytics, 2023)
This study aims to analyze the effect of Lifestyle, Promotion, and Product Quality on purchasing decisions on Nu Skin TR90 products in Surabaya. This study used a research tool or instrument in a questionnaire. In this study, a sample collection technique was used using the purposive sampling method. The total number of indicators in this study totaled 17 indicators and the parameters in the sample measurement to be used were 7. Data analysis used in this study used the component-based Structural Equation Modeling (SEM) method with using the Partial Least Square (PLS) analysis tool. Based on the results of the research that has been done, it is found that the Lifestyle variable has a non-significant effect on purchasing decisions. Promotion variable has a significant effect on purchasing decisions. Product Quality variable has a significant effect on purchasing decisions.